Budaya Organisasi dan Loyalitas Kerja yang dimediasi oleh Komitmen Kontinu - Thamrin Thamrin (Kontigensi : Jurnal Ilmiah Manajemen, 2018)
This study aims to investigate organizational culture and work loyalty that is mediated by continuance commitment. The research method used is a quantitative approach with Structural Equation Modeling (SEM) analysis techniques. The population in this study were lecturers in the Private College of Information Technology Study Program in Medan City with a sample of 152 people. The results of the study prove that there is an influence of organizational culture on work loyalty that is mediated by continuance commitment. The research implications suggest optimizing organizational culture and continuance commitment so that work loyalty can achieve optimally.